Genetic basis of the association of resistance genes mef(I) (macrolides) and catQ (chloramphenicol) in streptococci - Mingoia, Marina; Morici, Eleonora; Brenciani, Andrea; Giovanetti, Eleonora; Varaldo, Pietro E. (Frontiers in Microbiology, 2015)
In streptococci mef(I) and catQ, two relatively uncommon macrolide and chloramphenicol resistance genes, respectively, are typically linked in a genetic module designated IQ module. Though variable, the module consistently encompasses, and is sometimes reduced to, a conserved 5.8-kb mef(I)-catQ fragment. The prototype IQ module was described in Streptococcus pneumoniae. IQ-like modules have subsequently been detected in Streptococcus pyogenes and in different species of viridans group streptococci, where mef(E) may be found instead of mef(I). Three genetic elements, one carrying the prototype IQ module from S. pneumoniae and two carrying different, defective IQ modules from S. pyogenes, have recently been characterized. All are integrative and conjugative elements (ICEs) belonging to the Tn5253 family, and have been designated ICESpn529IQ, ICESpy029IQ and ICESpy005IQ, respectively. ICESpy029IQ and ICESpy005IQ were the first Tn5253 family ICEs to be described in S. pyogenes. A wealth of new information has been obtained by comparing their genetic organization, chromosomal integration, and transferability. The origin of the IQ module is unknown. The mechanism by which it spreads in streptococci is discussed.